Goodbye, homo sovieticus: Considerations about the Svetlana Alexievich’s Documentary Novel Secondhand time - Stępniak, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
This article concerns the problem of the phenomenon of the Soviet man – a product of the Soviet era, who is a complex, ambiguous and tragic ﬁgure. Svetlana Alexievich devotes the fifth book in the series Voices from Utopia to the Soviet man. On one hand, people brought up by the “red” civilization (as Alexievich deﬁnes them) were shaped by participation in revolution, wars and violence, which makes them ready to inﬂict it. On the other hand, they are fanatically attached to communist ideals, even when they have failed them. They ﬁnd it diﬃcult to ﬁnd themselves in the new reality. They are also incapable of using freedom, democracy and prosperity properly. The image of homo sovieticus in Alexievich’s documentary novel is depressing and sad – it is diﬃcult to understand someone who has survived the camps, torture, loss of relatives and the collapse of the empire, who patiently endures suﬀering inanticipation of happiness that he has never known, and who misses the USSR with its imperfections and enslavement.